2023
DOI: 10.3389/fvets.2023.1048067
|View full text |Cite
|
Sign up to set email alerts
|

The impact of curcumin on livestock and poultry animal's performance and management of insect pests

Abstract: Plant-based natural products are alternative to antibiotics that can be employed as growth promoters in livestock and poultry production and attractive alternatives to synthetic chemical insecticides for insect pest management. Curcumin is a natural polyphenol compound from the rhizomes of turmeric (Curcuma spp.) and has been suggested to have a number of therapeutic benefits in the treatment of human diseases. It is also credited for its nutritional and pesticide properties improving livestock and poultry pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 147 publications
0
11
0
Order By: Relevance
“…Many commercially available products aiming to improve broiler productive performance have been developed based on documented benefits of different PFA. However, the doses used in most in vivo studies reported in the literature can be up to ten times greater than commercial suitable doses recommended in the poultry industry ( Alagawany et al, 2022 ; Zaker-Esteghamati et al, 2020 ; Rahman et al, 2022 ; Surai and Surai, 2023 ; Sureshbabu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many commercially available products aiming to improve broiler productive performance have been developed based on documented benefits of different PFA. However, the doses used in most in vivo studies reported in the literature can be up to ten times greater than commercial suitable doses recommended in the poultry industry ( Alagawany et al, 2022 ; Zaker-Esteghamati et al, 2020 ; Rahman et al, 2022 ; Surai and Surai, 2023 ; Sureshbabu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Silymarin, betaine, and turmeric extracts have been extensively studied because of their benefits, which have been summarized in many reviews ( Yarru et al, 2009 ; Akhavan-Salamat and Ghasemi, 2016 ; Zaker-Esteghamati et al, 2020 ; Nawab et al, 2020 ; Mishra et al, 2021 ; Abd El-Hack et al, 2021 ; Abd El-Ghany and Babazadeh, 2022 ; Alagawany et al, 2022 ; Ugo et al, 2022 ; Elnesr et al, 2023 ; Gana et al, 2023 ; Guerrini and Tedesco, 2023 ; Surai and Surai, 2023 ; Sureshbabu et al, 2023 ). Adding these active ingredients to livestock and poultry feed improves metabolism, reproduction, immunity, nutrient digestibility, fat metabolism and can alleviate chronic liver injuries and mitigate the detrimental effects of heat stress, improving overall health and favoring animal growth and development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of the study totals in Table (6) indicated that there was no significant difference between them at the beginning of the experiment. While at the middle of the experiment, the T2 group recorded a significant decrease in their rates compared to the control group, and for the T4 group, their rates recorded a significant decrease compared to the rest of the groups.…”
Section: Alanine Aminotransferasementioning
confidence: 92%
“…According to research, adding curcumin to dairy products improved storage stability by increasing their antioxidant activity [5]. Moreover, curcumin contains antioxidant capabilities that enable it to give electrons and has phenol moieties that bind to free radicals, reducing cellular damage in animal organisms [6]. Animal production has made use of curcumin, mostly in ruminant feed [7].…”
Section: Introductionmentioning
confidence: 99%